Application of aptamer functionalized nanomaterials in targeting therapeutics of typical tumors - Yin, Xiujuan; He, Zhenqiang; Ge, Weiying; Zhao, Zhenhua (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer is a major cause of human death all over the world. Traditional cancer treatments include surgery, radiotherapy, chemotherapy, immunotherapy, and hormone therapy. Although these conventional treatment methods improve the overall survival rate, there are some problems, such as easy recurrence, poor treatment, and great side effects. Targeted therapy of tumors is a hot research topic at present. Nanomaterials are essential carriers of targeted drug delivery, and nucleic acid aptamers have become one of the most important targets for targeted tumor therapy because of their high stability, high affinity, and high selectivity. At present, aptamer-functionalized nanomaterials (AFNs), which combine the unique selective recognition characteristics of aptamers with the high-loading performance of nanomaterials, have been widely studied in the field of targeted tumor therapy. Based on the reported application of AFNs in the biomedical field, this paper first introduces the characteristics of aptamer and nano-materials and the advantages of aptamer-functionalized nano-materials, and then introduces the conventional treatment methods of glioma, oral cancer, lung cancer, Breast cancer, liver cancer, colon cancer, pancreatic cancer, ovarian cancer and prostate cancer and the application of AFNs in targeted therapy of these tumors. Finally, we discuss the progress and challenges of AFNs in this field.